Identify the most important parameters affecting the safety performance of mega projects in Iran’s construction industry (Using Fuzzy Analytic Hierarchy Process) - A Ardeshir; AH Khalilianpoor; Q Bagheri; Y Alipouri (Salāmat-i kār-i Īrān, 2016)
Background and aims: Construction industry is one of the riskiest industries all around the world and safety improvement in this industry is one of the main priorities in any country. A lot of researchers try to identify different factors that affect the safety. However, due to the large volume of high liquidity and volume of work in megaproject, identifying contributing factors to their safety is very important. So the main objective of this study was to identify and prioritize the factors affecting mega project in Iran.